Diversity of Ectoparasites in Native Chicken (Gallus gallus Domesticus) in Mandau Duri District, Riau - Santri Komala Asyfa; Radith Mahatma (Jurnal Biologi Tropis, 2023)
Native chicken (Gallus gallus domesticus) is a livestock animal that is widely kept by the community because it is very easy to maintain. Native chickens are widely used as a staple food that contains animal protein. This study aims to determine the prevalence and intensity of ectoparasite attacks and describe the types of ectoparasites found in native chickens in Mandau Duri District, Riau. The research was conducted in December 2022-February 2023. This study used random sampling method. Identification of ectoparasites was analyzed descriptively with book references, data analysis was calculated by the prevalence and intensity formulas. The results of the study found three species of ticks namely Menopon gallinae, Menacanthus stramineus and Menacanthus cornutus. The calculation results showed the highest prevalence and intensity in Menopon gallinae (32.5% and 3.62), the lowest prevalence and intensity in Menacanthus cornutus (25% and 3.1). The total prevalence of ectoparasites (87.5%) was categorized as common with moderate infection and the total intensity (9.72) was categorized as moderate.